2021
DOI: 10.3390/min11070755
|View full text |Cite
|
Sign up to set email alerts
|

Grey Box Modelling of Decanter Centrifuges by Coupling a Numerical Process Model with a Neural Network

Abstract: Continuously operating decanter centrifuges are often applied for solid-liquid separation in the chemical and mining industries. Simulation tools can assist in the configuration and optimisation of separation processes by, e.g., controlling the quality characteristics of the product. Increasing computation power has led to a renewed interest in hybrid models (subsequently named grey box model), which combine parametric and non-paramteric models. In this article, a grey box model for the simulation of the mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…The solid content rate at different rotational speeds was shown in Figure 17. It could be found that the separation performance was increased with the increase of the rotational speed, which was consistent with the results in the literatures 30,31 . Higher rotational speed resulted in increased centrifugal force, so the solid–liquid separation process could be completed in time in the drum.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The solid content rate at different rotational speeds was shown in Figure 17. It could be found that the separation performance was increased with the increase of the rotational speed, which was consistent with the results in the literatures 30,31 . Higher rotational speed resulted in increased centrifugal force, so the solid–liquid separation process could be completed in time in the drum.…”
Section: Resultssupporting
confidence: 90%
“…It could be found that the separation performance was increased with the increase of the rotational speed, which was consistent with the results in the literatures. 30,31 Higher rotational speed resulted in increased centrifugal force, so the solidliquid separation process could be completed in time in the drum. However, when the rotational speed was greater than 3000 rpm, the improvement in the separation performance was not obvious.…”
Section: Separation Performancementioning
confidence: 99%
“…In contrast to these two models, grey box models utilize semi-empirical equations derived from the experimental data, balancing between complex and simple solutions [73,74]. Machine learning-assisted CFD simulation, which is a combination of black box and white box models, is referred to as grey box models [75].…”
Section: Applications Potentials and Hurdles Of Pemfc System Integrationmentioning
confidence: 99%
“…In addition, Yang proposed the use of the well-known grey-box modeling that is being used in various other fields as well [54][55][56][57][58]. A figure indicating a grey-box model is depicted in Figure 2.…”
Section: Current Digital Twin Applications In 3d Printing Technologiesmentioning
confidence: 99%